Analysis of Chinese Automotive Firms’ Outbound Mergers and Acquisitions: The case of Geely and BAIC - Zhou, Siyu (2015)
For emerging market firms, outbound mergers and acquisitions can be deemed as one of the most effectual mode to achieve the internationalization goals. More and more automobile firms seek cross-border M&A opportunities and they explore more efficient approach of managing the post-acquisition integration process. This dissertation aims to conduct researches about Chinese automobile industry’s outbound M&As and specifically scrutinize the post-acquisition integration practices and performances. A multi-case study is introduced to address the research questions. Two Chinese automobile firms, Geely Holding Group and Beijing Automobile (BAIC) are selected as main research objects. The findings indicate that outbound M&A implies not only a shortcut for internationalization, but also a strategic consideration for long-term development for Chinese automobile firms. The firms do not fully follow an incremental path for global involvement; instead, they capture every single acquisition opportunities to enhance self-capabilities. Firms with abundant prior knowledge could cope with cross-culture transactions properly, but they mainly adopt the ‘light-touch’ integration strategy to deal with cultural differences and reduce integration risks. The strong combinative capability and cultural compatibility are of crucial significance for the whole integration practices as well. Geely and BAIC are relatively successful practical acquisition cases, and they are of nutritious meanings for Chinese auto industry’s cross-border M&A integration practices.